Digital Zakat and Islamic Fintech: A Bibliometric Analysis of Global Research Trends and Collaboration Networks (2012–2025) - Dupi, Muhamad; adzimatinur, fauziyah (Journal Of Middle East and Islamic Studies, 2025)
This paper examines global research trends, collaborative networks, and prevailing themes in digital zakat and Islamic fintech studies published from 2012 to 2025. We retrieved a total of 194 Scopus-indexed publications using bibliometric methods on September 23, 2025, and analyzed them using VOSviewer version 1.6.20. The analysis set a minimum occurrence threshold of 5 for keywords and a minimum citation threshold of 10 for documents. The results indicate that the number of publications has been steadily rising since 2017, with the most in 2023 (42 documents). Malaysia, Indonesia, and Nigeria were the top contributors, and INCEIF University and the International Islamic University Malaysia were the main places where people worked together. The Journal of Islamic Accounting and Business Research and the International Journal of Islamic and Middle East Finance and Management were the two most active places to publish. Keyword analysis shows that the most important topics are zakat, fintech, financial inclusion, blockchain, and sustainable development. Recent research is focusing increasingly on new technologies and the world after COVID-19. The results indicate that digital zakat and Islamic fintech lead to more open and fair financial practices.